THE BLESSED CITIES OF ISLAM : MECCA - MEDINA - Aksoy, Omer Faruk (New Jersey : The Light Inc., 2007)
Mecca and Medina are the two sanctuaries of Islam, places which every Muslim dreams of visiting at least once in a lifetime. Mecca is believed to be the very first location of human settlement and it was the birthplace of the Prophet Muhammad, peace be upon him. The Ka'ba, found in Mecca, was raised by the Prophet Abraham from its foundations to become the direction of prayer for believers. Medina is the city in which Islamic civilization was centralized and flourished religiously, politically, and socially. Faruk Aksoy, a BBC cameraman, took hundreds of photographs of these blessed cities from the most spectacular angles. This album includes over 160 select pictures shot by Aksoy since 1980s. He provides for us a picturesque pilgrimage experience and gives us an opportunity to share in the blessings of a lifetime journey as we browse through the pages accompanied by inspirational text by Fethullah Glen.
Originally published in Turkish as Mekke - Medine: Islam' in Iki Kutsal Sehri 2006
Keywords: Mecca (Saudi Arabia) -- Pictorial works; Medina (Saudi Arabia)